2011
DOI: 10.1039/c0cp02506b
|View full text |Cite
|
Sign up to set email alerts
|

Geometries, stabilities, and electronic properties of Pt-group-doped gold clusters, their relationship to cluster size, and comparison with pure gold clusters

Abstract: A systematic study of bimetallic Au(n)M(2) (n = 1-6, M = Ni, Pd, and Pt) clusters is performed by using density functional theory at the B3LYP level. The geometric structures, relative stabilities, HOMO-LUMO gaps, natural charges and electronic magnetic moments of these clusters are investigated, and compared with pure gold clusters. The results indicate that the properties of Au(n)M(2) clusters for n = 1-3 diverge more from pure gold clusters, while those for n = 4-6 show good agreement with Au(n) clusters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The HOMO‐LUMO gap is an important parameter which determines the chemical reactivity and stability of the metal clusters . The properties of the clusters fluctuate with the odd‐even number of doped gold atoms ,. Thus the order of stability is Au 3 Ni>AuNi 3 >Au 2 Ni 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HOMO‐LUMO gap is an important parameter which determines the chemical reactivity and stability of the metal clusters . The properties of the clusters fluctuate with the odd‐even number of doped gold atoms ,. Thus the order of stability is Au 3 Ni>AuNi 3 >Au 2 Ni 2 .…”
Section: Resultsmentioning
confidence: 99%
“…investigated the structural and electronic properties of small Au m Ni n (m+n≤6) clusters, and concluded that the reactivity of Au−Ni bimetallic clusters towards small molecules is higher than the pure gold clusters. The DFT studies had been shown that the fluctuation of the properties follows the odd‐even oscillation for the bimetallic Au n M 2 (n=1‐6, M=Ni, Pd, and Pt) clusters . The deposition of small bimetallic Cu 3 Au, Cu 7 Ni 3 , Ni 3 Pd 2 , Au 3 Ni and Ni 3 Au clusters on amorphous graphite surface are investigated experimentally applying electron microscopy and photoelectron spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the lowest-energy structures of Au n+1 (n=1-9) cluster system are in great agreement with the previous results. [20,22,28,[65][66][67][68][69][70][71] The averaged atomic binding energies, E b (n), attachment energies, ΔE(n), second-order difference of energies, Δ 2 E(n), vertical ionization potential, VIP, vertical electron affinity, VEA, chemical hardness, η, and the highest occupied-lowest unoccupied molecular orbital (HOMO-LUMO) gaps of pure gold clusters are also calculated and compared with the corresponding values of the Au n C (n=1-9) clusters. In addition, to provide effective guidelines for future experimental studies, we also calculated the vibrational frequencies for the lowest-energy structures of Au n C (n=1-9) clusters, which are listed in Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] Due to the significant role in catalysis and nanotechnology, the gold clusters have been and continued to become an increasingly interesting topic of research from both fundamental and practical viewpoints. So far there have been a large amount of experimental and theoretical studies on the pure gold clusters with impurity atom X, [27][28][29][30][31][32][33][34][35][36][37] and the most common are the transition metal impurities. In addition, as for the number of the dopant atoms, the single-doped situation predominates compared to the double-doped even triple-doped situation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the Au n M 2 (M = Pd, Pt; n = 1-4) clusters, Au n Ni 2 clusters show an inverse odd-even alternation phenomenon in magnetic property. 30 A density functional theory (DFT) study of Au n M 2 (M = Si, P; n = 1-8) clusters 31 indicates that the most stable isomers for Au n Si 2 and Au n P 2 (n = 1-8) clusters prefer a 3D structure when n is equal to or greater than 2 and 3, respectively. For single doping, Wang and co-workers reported that isoelectronic replacement of Au by Cu or Ag changes the onset of the 2D to 3D structural transition to a smaller size.…”
Section: Introductionmentioning
confidence: 99%